“Waxing the Knees of the Gods” in Juvenal (10. 55) and Prudentius (Apoth. 457) - Keyer, Denis (Hyperboreus, 2025)
The phrase genua incerare deorum in Iuv. 10. 55 is not related to the practice of attaching wax tablets with vows to statues of gods: (1) this metaphor would be far-fetched; (2) the tablets were attached to thighs, not knees; and (3) the tablets affixed to statues were sealed and contained secret vows, which does not fit Juvenal’s context.Instead, it refers to the praying gesture of clasping the addressee’s knees by analogy with waxing techniques, the verb incerare functions as a metaphor for rubbing, and with regard to the knees, ‘rubbing’ implies intensive touching: cf. genua (con)fricare in Pl. Asin. 670; 678. Prudentius’ genua incerare Dianae (Apoth. 447) suggests the same interpretation.Conversely, waxing images in Prud. c. Symm. 1. 203 and Ham. 404 is unrelated to Iuv. 10. 55, being connected instead to Iuv. 12. 88 (of the images of Lares). Chr. Gnilka’s suspicion that Prudentius was ignorant of pagan cultic practices is unfounded.Nuda in Vitruv. 7. 9. 4 is problematic and, in view of the close lexical parallelism with Plin. NH 33. 122 (nitescunt), should be emended to nitidanda.